Merçi de m'aider ex1) a)(+4)+(+2)= b)(-3)+(-12)= c)(-6)+(+2)= d)(+7)+(-12)= e)(+9,2)+2,5= f)(-0,4)+(-1,6)= ex2) A=(-3)+(+5)+(-14)+(-7)= B=(+12)+(+8)+(-13)+(-9)= C=(-14)+(-7)+(+2)+(-5)+(+7)= je remerçie ceux qui pourrons m'aider












































2

Réponses

  • Utilisateur Brainly
2014-09-06T20:16:08+02:00
Ex 1 :

A= (+ 4) + (+ 2)
A= 4 + 2
A = 6

B= (- 3) + (- 12)
B= - 3 - 12
B= - 15

C= (- 6) + (+ 2)
C= - 6 + 2
C= - 4

D= (+ 7) + (- 12)
D= 7 - 12
D= - 5

E= (+ 9,2) + 2,5
E= 11,7

F= (- 0,4) + (- 1,6)
F= - 0,4 - 1,6
F= - 2

Ex 2 :

A= (- 3) + (+ 5) + (- 14) + (- 7)
A= - 3 + 5 - 14 - 7
A= 5 - 24
A= - 19

B= (+ 12) + (+ 8) + (- 13) + (- 9)
B= 12 + 8 - 13 - 9
B= 20 - 22
B= - 2

C= (- 14) + (- 7) + (+ 2) + (- 5) + (+ 7)
C= - 14 - 7 + 2 - 5 + 7
C= 9 - 26
C= - 17
2014-09-06T20:24:23+02:00
Exercice 1 a)(+4) + (+ 2)= 4 + 2 = 6
b)(-3) + (-12) = - 3 - 12 = - 15

c)(- 6) + (+ 2) = - 6 + 2 = - 4

d)(+ 7) + (- 12) = 7 - 12 = - 5

e)(+ 9,2) + 2,5 = 11,7
f)(- 0,4) + (- 1,6) = - 0,4 - 1,6 = - 2

Exercice 2
A = (- 3) + (+ 5) + (- 14) + (- 7)
A = - 3 + 5 - 14 - 7
A = - 3 - 14 - 7 + 5
A = - 24 + 5
A = - 19

B = (+ 12) + (+ 8) + (- 13) + (- 9)
B = 12 + 8 - 13 - 9
B = 20 - 22
B = - 2

C = (- 14) + (- 7) + (+ 2) + (- 5) + (+ 7)
= - 14 - 7 + 2 - 5 + 7
= - 14 - 7 - 5 + 2 + 7
= - 26 + 9
= - 17